The Laccotrephes robustus Stål, 1871 (Hemiptera: Nepidae: Nepinae) in Vietnam, with notes on its’ morphological and DNA analyses - Nguyen, Dai Dac; Phan, Thi Giang; Ha, Ngoc Linh; Nguyen, Quang Cuong; Nguyen , Thi Hanh; Nguyen , Thanh Manh; Sergey, Ryndevich; Truong, Xuan Lam (Academia Journal of Biology, 2024)
The genus Laccotrephes Stål, 1865 has been known in Vietnam with four species, Laccotrephes grossus (Fabricius, 1787), Laccotrephes longicaudatus Nieser, Zettel & Chen, 2009, Laccotrephes pfeiferiae (Ferrari, 1888) and Laccotrephes simulatus Montandon, 1913. The species Laccotrephes robustus Stal, 1871 is a species endemic to the Philippines, first recorded in Vietnam from specimens collected in Cao Bang, Bac Kan and Nghe An provinces. The occurrence of L. robustus in Vietnam was confirmed by morphological and molecular data.